2013
DOI: 10.1016/j.jpsychores.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed and comorbid disorders in patients with presumed chronic fatigue syndrome

Abstract: A multidisciplinary approach to presumed CFS yields unequivocal CFS in only a minority of patients, and reveals a broad spectrum of exclusionary or comorbid conditions within the domains of sleep medicine and psychiatry. These findings favor a systematic diagnostic approach to CFS, suitable to identify a wide range of diagnostic categories that may be subject to dedicated care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
3
43
1
2
Order By: Relevance
“…15 Mariman et al (2013) showed that only 23.3% of the patients with chronic unexplained fatigue referred to a tertiary care center, were diagnosed with unequivocal CFS. 17 In 21.1% of the patients, CFS was associated with a sleeping disorder and/or psychiatric disorder. Obstructive sleep apnea (OSA) was the most common sleeping disorder (28.7%) while a mood disorder was the most common psychiatric comorbidity (26.5%).…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…15 Mariman et al (2013) showed that only 23.3% of the patients with chronic unexplained fatigue referred to a tertiary care center, were diagnosed with unequivocal CFS. 17 In 21.1% of the patients, CFS was associated with a sleeping disorder and/or psychiatric disorder. Obstructive sleep apnea (OSA) was the most common sleeping disorder (28.7%) while a mood disorder was the most common psychiatric comorbidity (26.5%).…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…39 found a sleeping disorder to be present in 18.6% of the CFS patients, 22.2% were not diagnosed with CFS because of a predominant sleeping disorder. 17 OSA was the most prevalent sleeping disorder (28.7% of the patients). A comparative study by Libman et al found no significant differences between CFS patients with and without OSA regarding subjective sleep variables and CFS symptoms.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Insomnia can be defined as the subjective experience of disturbed or non-restorative sleep that gives rise to daytime impairment despite adequate opportunity and circumstances for sleep (4,5). Despite its high prevalence, insomnia is often overlooked in clinical settings (6), and it is underdiagnosed in patients with CFS (7).…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly pertinent for the CFS population given that the symptom profile can overlap considerably with other conditions, including insomnia, and patients often present with comorbidities [37]. This presents a challenge for adequately evaluating intervention effectiveness in this group and underscores the importance of full description and justification of inclusion/exclusion criteria in prospective treatment studies.…”
Section: The Current Evidence For the Effect Of Get And Cbt On Sleepmentioning
confidence: 99%